ANALISIS EMPIRIS ATAS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PADA PERUSAHAAN PUBLIK NON KEUANGAN DI INDONESIA TAHUN 2009 - 2011 - , Nurikhsanti Khairani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the determinants of capital structure on Non- Financial Companies listed on the Indonesia Stock Exchange. The samples in this study were all non-financial companies listed on the index Kompas100 for 6 semesters in a row from 2009 to 2011 as many as 128 companies. The data analysis technique used is multiple linear regression analysis using panel data. Determinants of capital structure for this study are profitability, tangibility, tax, company size, non-debt tax shield, company growth, and business volatility. They are analyze in regards their influence to long term debt, short term debt, and the total debt. The results of this study indicate that profitability and tangibility have influence significantly both on short term debt and long term debt. While the company size, and business volatility have influence significantly both on shortterm debt and total debt, and non-debt tax shield has influence significantly only on long-term debt.